1987
DOI: 10.1038/326298a0
|View full text |Cite
|
Sign up to set email alerts
|

Alternative pathway activation of T cells by binding of CD2 to its cell-surface ligand

Abstract: Activation of resting T lymphocytes is initiated by the interaction of cell-surface receptors with their corresponding ligands. In addition to activation through the CD3 (T3)-Ti antigen-receptor complex, recent experiments have demonstrated induction of T-cell proliferation through the CD2 (T11) molecule, traditionally known as the erythrocyte(E)-receptor, through which T cells can bind red blood cells (RBC). This 'alternative pathway' of T-cell activation was observed in vitro in response to combinations of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
99
0
2

Year Published

1988
1988
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(105 citation statements)
references
References 16 publications
4
99
0
2
Order By: Relevance
“…Similarly, Hunig et al recently activated peripheral blood T cells with LFA-3+ sheep erythrocytes in concert with certain anti-CD2 antibodies (46). Finally, we and other investigators recently have shown that purified LFA-3 antigen plus the antLCD2 antibody 9-1 can directly activate peripheral T cells, and that purified LFA-3 antigen directly interacts with purified CD2 antigen (refs.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Similarly, Hunig et al recently activated peripheral blood T cells with LFA-3+ sheep erythrocytes in concert with certain anti-CD2 antibodies (46). Finally, we and other investigators recently have shown that purified LFA-3 antigen plus the antLCD2 antibody 9-1 can directly activate peripheral T cells, and that purified LFA-3 antigen directly interacts with purified CD2 antigen (refs.…”
Section: Discussionsupporting
confidence: 61%
“…Similar to thymocyte binding to thymic epithelial cells (39), binding of cultured synovial cells to thymocytes was inhibited by antibodies against synovial cell LFA-3 antigens and T cell CD2 molecules (Figure 1). These observations are of particular interest since thymocytes are capable of being triggered to proliferation by CD2 molecules, and the CD2 pathway of thymocyte activation is thought to be important in driving T cell maturation (46,47). Other peripheral stromal microenvironments such as tonsil and skin have been implicated in promoting the terminal stages of T cell maturation (reviewed in ref.…”
Section: Discussionmentioning
confidence: 99%
“…However, CD2 also displays part of it e¡ect through speci¢c signals conveyed by its cytoplamic tail, which can also be mobilized by speci¢c combination of mAb (Hunig et al 1987). CD2 signalling acts through regulation of di¡erent tyrosine kinases in the TCR^CD3 complex or independently of them.…”
Section: Targeting Lfa-1 and Cd2 Molecules (A) Inhibition Of Lfa-1^icmentioning
confidence: 99%
“…In fact, a complex pattern of signalling can be delivered to the T cell via CD2, probably determined by the conformational changes imposed on this molecule . A ligand for CD2 has been identified on sheep erythrocyte surface as being a 42 kd protein, termed T1 lTS (Hunig et al, 1987). The human cell surface equivalent for T IITS is the LFA3 molecule, a glycoprotein of mol.…”
Section: Introductionmentioning
confidence: 99%